(untitled) (Al-Farooq Journal of Sciences, 2026)
Context contributes to clarifying the meaning of words because it plays a prominent role in arriving at meaning through the structure created by the sender. This structure depends on the nature of usage and the intended purpose. Meaning varies according to the connection and use of words, with context precisely defining meaning. Therefore, no structure can be studied in isolation from its context, as it is the fundamental element in clarifying linguistic meaning, which leads to a diversity of contexts. A word acquires its precise meaning through its position within the structure, where words are arranged harmoniously to provide a complete meaning and a benefit that contributes to clarifying the intended meaning and removing ambiguity. This arrangement and interrelationship form multiple contexts, both internal and external, which the sender gives to the text. These contexts are then incorporated, highlighting aesthetic imagery, the temporal and spatial environment, and the circumstances surrounding the creation of the text and its purpose.